STRUKTUR KOMUNITAS MAKROZOOBENTOS DI ZONA INTERTIDAL DESA PINTU AIR KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Arif Nuhalin Nasution; Hesti Wahyuningsih; Indra Lesmana (AQUACOASTMARINE, 2017)
Pintu Air Village is an area that has an intertidal zone which is a tidal and tall area that has a very large diversity of macrozoobenthos. This research aims to Analysis of macrozoobenthic community structures and their chemical physics relationships in the intertidal zone. The research was conducted at the Intertidal Zone of Pintu Air Village in May-June 2017. Determination of sampling location using purposive sampling method at 3 stations. Taking Macrozoobenthos on 9 plots in the intertidal zone. Results of the research obtained 19 species of macrozoobenthos. Density ranged from 7,6-11,7 ind/m2, Diversity ranged from 2,18-2,19 including the moderate category, Uniformity ranged from 0,54-0,58, Dominance ranged from 0,11-0,12 dan Distribution pattern ranged from 0,71-0,87. Pearson correlation results between the diversity of macrozoobenthos to temperature, depth and salinity are moderate, pH and brightness are low, DO is very low.Keyword : Pintu Air Village, Intertidal Zone, Macrozoobenthos, CommunityStructure, Water Quality.